Response of Tuberculosis to DOTS Therapy in People Living with HIV/AIDS: A Prospective Clinical Study - B. Bhargav Prasad; V.A. Narasimha Raju; P. Jayakar Babu (Journal of Clinical and Diagnostic Research, 2012)
Background: In the patients with HIV and concomitant tuberculosis (TB), the response to directly observed therapyshort course (DOTS) is variable because of immunosupression, opportunistic infections and intolerance due to drugs including anti-retroviral treatment (ART). Aim: To study the response of TB to DOTS in immunosupressed patients with HIV. Material and Methods: Patients who attended our department during 2009-2010 with respiratory symptoms were screened. Study group comprised patients diagnosed with HIV with TB. Study group was further divided in A-CD4 count <150/ cmm, receiving DOTS with ART and B- CD4 count >150/cmm, receiving DOTS alone. Control group comprised patients with TB alone, on DOTS. Results: Three hundred and forty three patients were diagnosed with TB of which 37, diagnosed with HIV with TB, were included in study (7 with CD4 count <150/cmm, receiving DOTS with ART and 30 with CD4 count >150/cmm, receiving DOTS alone). Control group comprised of 306 patients with TB alone, on DOTS. In the study group, of 7 patients in subgroup A, 2 patients died and 5 patients defaulted. All 30 patients in subgroup B were improved. Improvement was observed in all patients in control group. Conclusions: Concomitant use of DOTS and ART increase in the incidence of therapy default to DOTS otherwise six months of therapy is enough to cure TB in HIV cases.